Aerodynamic Analysis of Cup Anemometers Performance: The Stationary Harmonic Response. (4th December 2013) - Pindado, Santiago; Cubas, Javier; Sanz-Andrés, Ángel
Abstract : The effect of cup anemometer shape parameters, such as the cups' shape, their size, and their center rotation radius, was experimentally analyzed. This analysis was based on both the calibration constants of the transfer function and the most important harmonic term of the rotor's movement, which due to the cup anemometer design is the third one. This harmonic analysis represents a new approach to study cup anemometer performances. The results clearly showed a good correlation between the average rotational speed of the anemometer's rotor and the mentioned third harmonic term of its movement.